The wife as stranger in the family - Susara J. Nortjé-Meyer (HTS Teologiese Studies/Theological Studies, 2019)
The phenomenon of the stranger reveals that spatial relations are, on the one hand, only the condition and, on the other hand, the symbol of human relations. This article discusses the specific form of interaction of the wife (woman) as a stranger in the context of the biblical family. The wife as a stranger is discussed here not in the sense often touched upon in the past, as a wanderer who comes today and goes tomorrow, but rather as a person who comes today and stays tomorrow. She is, so to speak, the potential wanderer: although she has not moved on, she has also not overcome the freedom of coming and going. She is fixed within a particular spatial group, or within a group whose boundaries are similar to spatial boundaries, but her position in this group is determined by the fact that she never belonged to it from the beginning. The unity of nearness and remoteness involved in every human relation is organised, in the phenomenon of the stranger, in a way which may be most briefly formulated by saying that in her relationships, distance means that she, who is close by, is also far away, and her strangeness means that she, who is far away, is also actually near. I examined the implications of knowing and identifying the wife as a stranger for feminist theory and its interpretation.